Where the Demons Fell. A Manichaean Sogdian Manuscript in Sogdian Script from Mani’s Book of the Giants - Morano, Enrico (Journal of Iranian Linguistics, 2024)
Two unpublished Sogdian fragments in Sogdian Script of the Berlin Turfan collection, both from the same page and glassed together, contain a cosmogonic text on the falling of the demons/archons to the four directions of the earth and part of the myth of the creation of the protoplasts by the archdemons Šaqlūn and Pēsūs. This text will be proposed here as part of the Sogdian version of Mani’s Book of the Giants.